Fronteiras: paisagens, personagens, identidades - Márcio Santos (Revista de História, 2005)
GUTIÉRREZ, Horacio; NAXARA, Marcia R. C. e LOPES, Maria Aparecida de S. (orgs.). Fronteiras: paisagens, personagens, identidades. Franca: UNESP; São Paulo: Olho D´Água, 2003.